Value creation through quality and innovation – a case study on Portugal - Santos, Gilberto (2020)
Purpose The purpose of this paper is to analyze the best way to create value in Portugal through quality and innovation and also to check what needs to be improved. Design/methodology/approach A questionnaire was applied to population of 152 companies, with the research and development (R&D) management certified by Portuguese Standard NP 4457. The final sample was 66 companies, which correspond to 45 percent of the population. Statistical analysis of the data collected was performed using IBM SPSS Statistical Software. Findings The authors highlighted the main reasons/motivations that led companies to implement the NP 4457, which were, among others, competitive advantage and creating value. The systematization of information and the generation and management of ideas were highlighted as the main advantages. The lack of methodologies for innovation management and knowledge management was the difficulty experienced in the implementation of NP 4457. Portugal needs to increase patent registration and it also needs to know how to take advantage of the investment made in R&D, in order to decrease the unit cost of knowledge. Portuguese engineering should be more about product design than production processes. The involvement of top management must be greater. Originality/value This investigation contributes to the innovation and quality body of knowledge, since it explores the complementarity between the two concepts as sources of value creation. This case study is one of the first Portuguese empirical research works about value creation through quality and innovation in Portugal. It also allows to know in detail the Portuguese business reality in terms of innovation management.